Acupuncture: Chinese therapeutic technique and its applications in dentistry (Research, Society and Development, 2024)
Objective: The objective of this article is to talk about acupuncture, showing its origin and history, showing how it works, creating an interface between this practice and dentistry, addressing the benefits of this technique in dental treatments. Methodology: To compose this review article, searches were carried out for studies, articles, monographs and gray literature books that could contain a large amount of information, enriching the manuscript, bringing more scientific and current basis, thus, these searches were carried out on the basis data such as: Science Direct, Web of Science, DeCs, Scielo, PROSPERO, The Brazilian Journal of Health Review, VHL/BIREME, CAPES Journal Portal, The Cochrane Library, PUBMED and Google Academy. Results: Acupuncture is an ancient technique, created in China and which has spread throughout the planet, being something that has great use within medicine and dentistry, in treating problems such as: orofacial pain, TMD, neuralgia of the trigeminal and having anesthesia and analgesia function. Conclusion: It was seen that acupuncture is a Chinese technique that has great utility within dentistry, with a range of benefits within problems that are commonly seen in the clinical life of a dental surgeon and that affect the health of several people during the throughout life, thus being a powerful tool when used appropriately by dentists who are trained in this technique.